AN OPTIMIZATION OF A SOLAR SAILCRAFT TRAJECTORY IN AN EARTH-MARS TRANSFER CONSIDERING THE ATTITUDE DYNAMICS - Lopes, Igor Mainenti; Souza, Luiz Carlos Gadelha de (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The goal of this work was to optimize the trajectory of a solar sailcraft in an Earth-Mars transfer. Solar sailcraft is propulsion system with great interest in space engineering,Â since it uses solar radiation to propulsion. So there is no need for propellant to be used, thusÂ it can remains active throughout the entire transfer maneuver. This type of propulsion systemÂ opens the possibility to reduce the cost of exploration missions in the solar system. In itsÂ simplest configuration, a Flat Solar Sail (FSS) consists of a large and thin structure generallyÂ composed by a film fixed to flexible rods. The performance of these vehicles depends largelyÂ on the sails attitude relative to the Sun. Using a FSS as propulsion, an Earth-Mars transferÂ optimization problem was tackled by the GEOÂ realÂ algorithm (Generalized ExtremalÂ Optimization with real codification). This algorithm is an Evolutionary Algorithm (AE) basedÂ on the theory of Self-Organized Criticality. The FSS was able to perform up to 10 maneuvers until reach Mars. Two angles values are necessary to characterize the FSS film normalÂ vector. Therefore, the GEOÂ realÂ algorithm had to optimize up to 20 design variables in order toÂ minimize the transfer time from Earth to Mars. Once the optimized control law and the FSSÂ trajectory were obtained, the attitude equations of motion were considered. Finally, theÂ impact of this consideration in the FSS control law performance was evaluated. Keywords: Solar sailcraft, Trajectory optimization, Evolutionary algorithm, AttitudeÂ dynamics, Generalized Extremal Optimization.